Transformasi Morfologis Nomina Corona, Delta, Omicron Pada Frasa Nomina dan Frasa Preposisi dalam Koran Daring Berbahasa Jerman - Dewi Ratnasari; Sudarmaji Sudarmaji (Ranah: Jurnal Kajian Bahasa, 2022)
The purpose of this research is to describe the morphological transformation of nouns in the construction of German noun phrases and prepositional phrases. Data collection was carried out through read, and note from predetermined data sources. The data corpus was obtained from online German language newspapers Zeit Online, Spiegel, and Morgenpost and analyzed using the Direct Element Division Technique (DEDT). The results of the analysis show that the compound nouns that appear have the following forms: (i) compound nouns with a hyphen “–“, (ii) compound nouns without a hyphen “–“, (iii) compound nouns with zero filling elements, (iv) orthographically several compound nouns are written in a combined way. The use of a hyphen “–“ is one way to vary the morphological construction of compound nouns which contain the nouns Corona, Delta, and Omikron. Several prepositional phrases, which contain only the nouns Corona, Delta, and Omicron, do not have delimiters in the form of determinants as gender markers, so that the nouns Corona, Delta, and Omicron are no longer visible, resulting in deletion of determinants as gender markers. It can be said that the nouns Corona, Delta, and Omikron provide flexibility to German users, especially in carrying out morphological transformations in the formation of other compound nouns with their various variations. AbstrakTujuan penelitian ini mendeskripsikan transformasi morfologis nomina dalam konstruksi frasa nomina dan frasa preposisi bahasa Jerman. Pengumpulan data dilakukan melalui baca, dan catat dari sumber data yang telah ditetapkan. Korpus data diperoleh dari koran daring berbahasa Jerman Zeit Online, Spiegel,dan Morgenpost dan dianalisis dengan cara Teknik Bagi Unsur Langsung (BUL). Hasil analisis memperlihatkan bahwa nomina majemuk yang muncul memiliki bentuk-bentuk: (i) nomina majemuk dengan tanda sambung “–“, (ii) nomina majemuk tanpa tanda sambung “–“, (iii) nomina majemuk dengan elemen pengisi nol, (iv) secara ortografis beberapa nomina majemuk ditulis dengan cara digabungkan. Penggunaan tanda sambung “–“ merupakan salah satu cara memvariasikan konstruksi morfologis nomina majemuk yang berunsur nomina Corona, Delta, dan Omikron. Beberapa frasa preposisi, yang berunsur hanya nomina Corona, Delta, dan Omikron, tidak memiliki pewatas berupa determinan sebagai pemarkah gender, sehingga gender nomina Corona, Delta, dan Omikron menjadi tidak terlihat, sehingga terjadi pelesapan determinan sebagai pemarkah gender. Dapat dikatakan bahwa nomina Corona, Delta, dan Omikron  memberikan keluwesan kepada pengguna bahasa Jerman khususnya untuk melakukan transformasi morfologis dalam pembentukan nomina majemuk lainnya dengan beragam variasinya.